Agrobacteria lacking ornithine lipids induce more rapid tumour formation. (9th September 2012) - Vences‐Guzmán, Miguel Ángel; Guan, Ziqiang; Bermúdez‐Barrientos, José Roberto; Geiger, Otto; Sohlenkamp, Christian
Summary Ornithine lipids (OLs) are phosphorus‐free membrane lipids that are widespread among Gram‐negative bacteria. Their basic structure consists of a 3‐hydroxy fatty acyl group attached in amide linkage to the α‐amino group of ornithine and a second fatty acyl group ester‐linked to the 3‐hydroxy position of the first fatty acid. It has been shown that OLs can be hydroxylated within the amide‐linked fatty acyl moiety, the secondary fatty acyl moiety or within the ornithine moiety. These modifications have been related to increased stress tolerance and symbiotic proficiency in different organisms such as Rhizobium tropici or Burkholderia cenocepacia. Analysing the membrane lipid composition of the plant pathogen Agrobacterium tumefaciens we noticed that it forms two different OLs. In the present work we studied if OLs play a role in stress tolerance and pathogenicity in A. tumefaciens. Mutants deficient in the OLs biosynthesis genes olsB or olsE were constructed and characterized. They either completely lack OLs (ΔolsB) or only form the unmodified OL (ΔolsE). Here we present a characterization of both OL mutants under stress conditions and in a plant transformation assay using potato tuber discs. Surprisingly, the lack of agrobacterial OLs promotes earlier tumour formation on the plant host.